Imbalance Between Interleukin-1β and Interleukin-1 Receptor Antagonist in Epicardial Adipose Tissue Is Associated With Non ST-Segment Elevation Acute Coronary Syndrome - Parisi, Valentina; Petraglia, Laura; Cabaro, Serena; D’Esposito, Vittoria; Bruzzese, Dario; Ferraro, Giusy; Urbani, Andrea; Grieco, Fabrizio Vincenzo; Conte, Maddalena; Caruso, Aurelio; Grimaldi, Maria Gabriella; de Bellis, Antonio; et al. (Frontiers in Physiology, 2020)
Introduction. Interleukin-1beta (IL-1β) is crucially involved in the pathogenesis of coronary atherosclerotic diseases (CAD) and its inhibition has proven cardiovascular benefits. Epicardial adipose tissue (EAT) is a local source of inflammatory mediators which may negatively affect the surrounding coronary arteries. In the present study, we explored the relationship between serum and EAT levels of IL-1β and IL-1 receptor antagonist (IL-1ra) in patients with chronic coronary syndrome (CCS) and recent acute coronary syndromes (ACS). Methods. We obtained EAT biopsies in 54 CCS (Group 1) and 33 ACS (Group 2) patients undergoing coronary artery bypass grafting. Serum and EAT levels of IL-1β and IL-1ra were measured in all patients. An immunophenotypic study was carried out on EAT biopsies and the CD86 events were studied as markers of M1 macrophages. Results. Circulating levels of IL-1β were significantly higher in the overall CAD population compared to a control group [7.64 pg/ml (6.86; 8.57) vs 1.89 pg/ml (1.81;2.29); p<0.001]. In contrast, no differences were observed for serum IL-1ra levels between CAD and controls. Comparable levels of serum IL-1β were found between Groups 1 and 2 [7.6 pg/ml (6.9; 8.7) vs 7.9 pg/ml (7.2; 8.6); p=0.618]. In contrast, significanltly lower levels of serum IL-1ra were found in Group 2 compared to Group 1 [274 pg/ml (220; 577) vs 603 pg/ml (334; 1022); p=0.035]. No differences of EAT levels of IL-1β were found between Group 2 and Group 1 [3.4 pg/ml (2.3; 8.4) vs 2.4 pg/ml (1.9; 8.0); p=0.176]. In contrast, significantly lower EAT levels of IL-1ra were found in Group 2 compared to Group 1 [101 pg/ml (40; 577) vs 1344 (155; 5327); p=0.002]. No correlation was found between EAT levels of IL-1β and CD86 and CD64 events. Conclusions. The present study explores the levels of IL-1β and IL-1ra in the serum and in EAT of CCS and ACS patients. ACS seems to be associated to a loss of the counter-regulatory activity of IL-1ra against the pro-inflammatory effects related to IL-1β activation.